The effect of treatment with Abscisic and gibberellic acid on physiological and activity of anti- oxidant enzymes of Lettuce plant under salt stress conditions (Damascus University Journal of agriculture sciences, 2025)
This experiment was carried out in Facuity of Agriculture – amascus university during The period from 2020-2021, to study The effect of treatment with Gibberellic acid and Abscisic acid on Some physiological and biochemical Characters of two species fo Letus  ( Kabbos and Shinshar ) under Stress Conditions.                                           Seeds were Soaked in Gibberellic acid(0, 50, 100 ppm) for 24h, then cultured in germination plates. Amix of Toarp and perlite(1:1) was used, And NaCl(0,50,100,150 mM) was added. One week after transplanting, Abscisic acid (0,5,10ppm) was Foliar sprayed Five times with seven days intervals.                                                                              This reseach contained of 20 treatment /specie/ where each treatment consist of three replicates with ten plants for each replicate. Data were calculated and evaluated using Compeletely Randomized Block Desingn, then analysied using Spss. The significant differces were evaluated on a level of 95%.                                                                           On the other side, treatment with Gibberellic acid and Abscisic acid increased the activity of anti- oxidant enzymes ( peroxidase, Catalase, SOD), The concentration of K and P. And decreased the concentration of N. The interaction treatment of  gibberellic acid (10ppm) resulted in the best values in all Studied parameters comparing with control which resulted in the lowest values.
Keywords: Lettuce; Salt Stress; Abscisic Acid; Gebrilic Acid; Physiological And Biochemical Characters